Status Kepemilikan dan Konflik Tanah di Sekitar Rel Kereta Api Surabaya Tahun 2013 - Mawardi Purbo Sanjoyo (heritage, 2021)
Every big city generally experiences problems related to living space availability. This problem also afflicts Surabaya, which is often pinned as the second-largest city in Indonesia. One of the space points that is considered able to fulfill the living space by the urban poor community is the area on the edge of the railroad tracks, or around the tracks. The confrontation between regulations and residential areas that violate these regulations causes a conflict between government institutions and the communities on the edge of the rail. This paper aims to examine the problem of land around the railroad tracks in the city of Surabaya in 2013.  The method used in this paper is the Historical Research Method. The result of this study is that the root cause of the land ownership conflict in Surabaya is the ownership of land certificates by the residents and binding rules at the national level. The residents own the certificate of eigendom verponding, as well as the green letter to be able to occupy the land, while the PT KAI is based on articles of railways. They demanded to stop the efforts to control the houses along the railroad tracks. In addition, they continue to defend every inch of land they own, until they receive a sense of justice from the authorities with commensurate compensation.